Composição química e aspectos morfológicos de mudas de Tabebuia chrysotricha (Standl.) produzidas em diferentes substratos e soluções de fertirrigação - Sarzi, Isabele; Villas Boas, Roberto Lyra [UNESP]; Silva, Magali Ribeiro da [UNESP] (Ipef-inst Pesquisas Estudos Florestais, 2008)
The work aimed to study the formation of Tabebuia chrysotricha Standl. seedlings in function of four substrates, varying the covering fertilization solutions. To compose the substrate it was used fibrous and granulated coconut fiber obtaining the following treatments: 100% fibrous (100% F), 60% fibrous + 40% granulated (60% F+40% G), 40% fibrous + 60% granulated (40% F+60% G) and 100% granulated (100% G). The basis fertilization was the same for all treatments and the solutions of covering fertilization varied in order to obtain complete solutions with electric conductivities of 1.06 dS m(-1), 2.12 dS m(-1), 3.2 dS m(-1) and 4.25 dS m(-1). The propagative material was sowed directly in plastic containers (120mL) with the respective substrates. The fertilization was received through sub-irrigation once a week, respecting the treatments of fertilizations. Seedlings produced in 100%G had been taller and higher than the others. The chemical analyses of aerial part were obtained when the seedlings were ready for expedition (height of 20 cm). The seedlings production in substrate 100% F and 60% F+40% G allowed them to have higher N, S, B, Mn and Zn concentrations in the aerial part. The production of T chrysotricha seedlings is recommended in granulated coconut fiber substrate and fertilizer solutions with EC of 1.06 dS m(-1)
Chemical composition and morphological aspects of Tabebuia chrysotricha (Standl.) seedlings produced in different substrate and fertirrigation's solutions
Keywords: Tabebuia chrysotricha; Electric conductivity; Forest nursery